Carbon Nanostructure-based Sensors: A Brief Review on Recent Advances. (3rd March 2019) - Bezzon, Vinícius D. N.; Montanheiro, Thaís L. A.; de Menezes, Beatriz R. C.; Ribas, Renata G.; Righetti, Victor A. N.; Rodrigues, Karla F.; Thim, Gilmar P.
Abstract : A brief review reporting the recent advances on the carbon nanostructured materials-based sensors covering recently published works is presented. Several works dealing with experimental and theoretical data are reviewed and discussed. The main results for carbon nanotubes, nanodiamonds, fullerene, graphene, and hybrid carbon-nanostructured devices that show sensing properties in different fields were considered for the discussions. The goal of this paper was to highlight sensor mechanisms, and the best results reached up to now are creating bases for further applications.